Evaluation of the Efficiency of Silica Removal in Effluents with (Zea Mays Var. Saccharata) in the Santa Rosa 94-1 Mining Concession in C.C. Llocllapampa, Jauja, Peru - Aliaga Zevallos, Deysi (2024)
In recent years in Peru, there are few non-metallic mining companies, one of the main ones being the Santa Rosa 94-1 mining concession, which is located in the community of Llocllapampa Jauja - Peru, where the main resource is silica sand that is used in this place, although it also generates a negative impact on the siliceous sand washing operation process since it modifies the conditions of the surface water since they do not have a treatment system. The objective of the research is to determine the efficiency and the amount of organic coagulant (Zea mays var. saccharata) for the removal of silica from the effluent in the mining concession. The characterization of the silica was carried out through petrographic analysis to know its composition, the effluent of the Total Suspended Solids (TSS) parameter was characterized, then it was designed factorially for 8 treatments with variation of the organic amendment, volume and time, which was applied to removal processes. After the analysis, they gave as a result that the non-metallic mining effluent generates a negative environmental impact on the ecosystem, comprising 15010 mg/L of TSS which exceeds the Maximum Permissible Limits, the combinations of organic amendment, effluent and time were developed, where in treatment 8 an average removal of 5,999 g/ml was obtained, which represents 88%, being the most efficient for silica removal.